Novel ion-exchange materials derived from poly(styrene-co-maleimide) and a study of the extraction and recovery of gold (III) chloride from acidic solutions - Lakay, Eugene Marlin (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.